2019
DOI: 10.1002/chem.201904147
|View full text |Cite
|
Sign up to set email alerts
|

Stafia‐1: a STAT5a‐Selective Inhibitor Developed via Docking‐Based Screening of in Silico O‐Phosphorylated Fragments

Abstract: We present a new approach for the identification of inhibitors of phosphorylation‐dependent protein–protein interaction domains, in which phenolic fragments are adapted by in silico O‐phosphorylation before docking‐based screening. From a database of 10 369 180 compounds, we identified 85 021 natural product‐derived phenolic fragments, which were virtually O‐phosphorylated and screened for in silico binding to the STAT3 SH2 domain. Nine screening hits were then synthesized, eight of which showed a degree of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…The hydrophilicity of the phosphate motifs was reduced by generating a pro-drug precursor, which employs pivaloyloxymethyl esters to conceal the negatively charged phosphate groups and increase cell penetrance. Recently, Natarajan et al reported Stafia-1, a selective inhibitor for STAT5A, discovered by docking-based screening [102]. Tested applications for STAT5 inhibitors in vivo and in vitro are summarized in Table 2.…”
Section: Stat5 Inhibitorsmentioning
confidence: 99%
“…The hydrophilicity of the phosphate motifs was reduced by generating a pro-drug precursor, which employs pivaloyloxymethyl esters to conceal the negatively charged phosphate groups and increase cell penetrance. Recently, Natarajan et al reported Stafia-1, a selective inhibitor for STAT5A, discovered by docking-based screening [102]. Tested applications for STAT5 inhibitors in vivo and in vitro are summarized in Table 2.…”
Section: Stat5 Inhibitorsmentioning
confidence: 99%
“…We recently presented catechol bisphosphates as the first chemical entities that inhibit STAT5b with selectivity over STAT5a [5] . Subsequently, we presented symmetrically substituted m ‐terphenyl phosphates as the first inhibitors of STAT5a which display selectivity over STAT5b [6] . The most potent and selective m ‐terphenyl phosphate‐based STAT5a inhibitor was dubbed Stafia‐1 ( 1 , Figure 1A), which inhibited STAT5a (K i =10.9±1.8 μM) with at least 9‐fold selectivity over STAT5b [6] .…”
Section: Figurementioning
confidence: 99%
“… A) Structure of Stafia‐1 and B) its suggested docking‐based mode of binding [6] to the X‐ray structure of murine STAT5a (PBD 1Y1U) [8] . The SH2 domain is shown in yellow, the linker domain is shown in light blue [10] .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Another example for a STAT5A/B SH2 domain inhibitor, IST5-002, blocked phosphorylation and nuclear translocation of STAT5A/B in BCR–ABL + in vitro and in vivo systems [164,176]. Via a virtual compound library screening approach and further structural adaptions, the first STAT5A SH2 domain inhibitor was identified, showing a modest reduction of pYSTAT5A levels in BCR–ABL + cells [177]. All compounds require further modifications to improve the bioavailability, stability, and potency.…”
Section: Direct Stat5a/b Inhibition Remains Challengingmentioning
confidence: 99%